Verbal Aggression: Between Violence and Impotence - Havryliv, Oksana (East European Journal of Psycholinguistics, 2017)
In this article a clear line between two terms "verbal aggression" - "verbal violence" is drawn. Based on the results of surveys case studies held by the author "verbal aggression" is viewed as a complex linguistic phenomenon, in the basis of which both intention aimed at humiliation of the addressee (then verbal aggression equals to verbal violence), and intentions that are not aimed at verbal violence and that we can call "efficient" may lie, since the necessity to communicate their negative emotions belongs to people’s communication (emotional function of language), to point at negative moments, not intending to offend the addressee. The "productive" functions of verbal aggression, emphasized in the field of psychology, are not sufficiently studied from linguistic perspective. Special attention in the article is given to the relation of verbal and physical aggression. Based on the theory of speech acts and the theory of performativity we view language as an action and distinguish two possibilities of aggressive speech acts: the one that is aimed at violence and the non-violent one. In the first case it is language of violence as a separate independent form of violence.References• Aman, R. (1972). Psychologisch-sprachliche Einleitung in das Schimpfen. In: Bayrisch-Österreichisches Schimpfwörterbuch, (S. 153-188). R. Aman (Hg.). München: Süddeutscher Verlag.• Bach, G. R., Goldberg, H. (1981). Keine Angst vor Aggression. Die Kunst der Selbstbehauptung. FaM: Fischer.• Biffar, R. (1994). Verbale Aggressionsstrategien. Analyse, Systematik, Anwendung. Aachen: Shaker.• Burgen, S. (1998). Bloody hell, verdammt noch mal! Eine europäische Schimpfkunde. München: Dt. Taschenbuch.• Butler, J. (2006). Haß spricht. Zur Politik des Performativen. FaM: Suhrkamp.• Cherubim, D. (1991). Sprache und Aggression. Krieg im Alltag – Alltag und Krieg. Loccumer Protokolle, 58, 11-35.• Devkin, V. D. (1996). Der russische Tabuwortschatz. Leipzig: Langenscheidt Enzyklopädie.• Ehalt, Ch. (2015). Vorwort. In: Schmäh als ästhetische Strategie der Wiener Avantgarde, (S. 7-10). Suchy, I., Krejci, H. (Hg.).Weitra: Bibliothek der Provinz.• Ermen, I. (1996). Fluch – Abwehr – Beschimpfung. Pragmatik der formelhaften Aggression im Serbokroatischen. FaM u.a.: Peter Lang.• Faust, M. (1970). Metaphorische Schimpfwörter. Indogermanische Forschungen, 74, 57-47.• Fiehler, R. (1990). Kommunikation und Emotion. Berlin u.a.: Walter de Gruyter. • Freud, S. (1994). Der Humor. In: S. Freud Studienausgabe Bd. IV, (S. 275-282). A. Mitscherlich, J. Strachey, A. Richards (Hg.). FaM: Fischer.• Gauger, H-M. (2012). Das Feuchte und das Schmutzige. Kleine Linguistik der vulgären Sprache. München: Beck.• Graber, H. G. (1931). Zur Psychoanalyse des Fluchens. Psychoanalytische Bewegung, 3, 57-68.• Havryliv, O. (2009). Verbale Aggression. Formen und Funktionen am Beispiel des Wienerischen. FaM, Wien u.a.: Peter Lang.• Herrmann, S. K., Krämer, S., Kuch, H. (Hg.). (2007). Verletzende Worte. Die Grammatik sprachlicher Missachtung. Bielefeld: Transcript.• Hess-Lüttich, E.W.B. (2008). HimmelHerrgottSakrament! Gopfridstutz! und Sacklzement! Vom Fluchen und Schimpfen – Malediktologische Beobachtungen. Kodikas/Code. An International Journal of Semiotics, 31(3-4), 327-337.• Holzinger, H. (1984). Beschimpfungen im heutigen Französisch. Pragmatische, syntaktische und semantische Aspekte. Ph.D. Dissertation: Universität Salzburg.• Kiener, F. (1983). Das Wort als Waffe. Zur Psychologie der verbalen Aggression. Göttingen: Vandenhoek & Ruprecht.• Kotthoff, H., Jashari, S., Klingenberg, D. (2013). Komik (in) der Migrationsgesellschaft. Konstanz und München: UVK Verlagsgesellschaft.• Krämer, S. (Hg.) (2010). Gewalt in der Sprache. Rhetoriken verletzenden Sprechens. München: Wilhelm Fink.• Liebsch, B. (2007). Subtile Gewalt. Weilerswirt: Velbrück Wiss.• Lötscher, A. (1980). Lappi, Lööli, blööde Siech! Schimpfen und Fluchen im Schweizerdeutschen. Frauenfeld: Huber.• Mokienko, V., Walter, H. (1999). Lexikographische Probleme eines mehrsprachigen Schimpfwörterbuchs. Anzeiger für slawische Philologie, XXVI, 199-210.• Opelt, I. (1965). Die lateinischen Schimpfwörter und verwandte sprachliche Erscheinungen. Heidelberg: Winter.• Rehbock, H. (1987). Konfliktaustragung in Wort und Spiel. Analyse eines Streitgesprächs von Grundschulkindern. In: Konflikte in Gesprächen, (S. 176- 238). G. Schank, J. Schwitalla (Hg.). Tübingen: Gunter Narr.• Schumann, H. B. (1990). Sprecherabsicht: Beschimpfung. Zeitschrift für Phonetik, Sprachwissenschaft und Kommunikationsforschung, 43, 259-281.• Schwarz-Friesel, M. (2013). Sprache und Emotion. Tübingen und Basel: Francke.• Searle, J. R. (1971). Sprechakte. Ein sprachphilosophischer Essay. FaM.: Suhrkamp.• Sornig, K. (1975). Beschimpfungen. Grazer Linguistische Studien, 1, 150- 170.• Українська мова без табу. Словник нецензурої лексики та її відповідників. К: Критика, 2008.• Wierzbicka, A. (1973). Problems of expression: Their place in the semantic theory. In: Recherches sur les sestemes Signifiants. Symposium de Varsovie 1968, (S. 145-164). The Hague: Mouton.• Жельвис В. И. Поле брани: cквернословие как социальная проблема в языках и культурах мира. М: Ладомир, 1997.References (translated and transliterated)• Aman, R. (1972). Psychologisch-sprachliche Einleitung in das Schimpfen. In: Bayrisch-Österreichisches Schimpfwörterbuch, (S. 153-188). R. Aman (Hg.). München: Süddeutscher Verlag.• Bach, G. R., Goldberg, H. (1981). Keine Angst vor Aggression. Die Kunst der Selbstbehauptung. FaM: Fischer.• Biffar, R. (1994). Verbale Aggressionsstrategien. Analyse, Systematik, Anwendung. Aachen: Shaker.• Burgen, S. (1998). Bloody hell, verdammt noch mal! Eine europäische Schimpfkunde. München: Dt. Taschenbuch.• Butler, J. (2006). Haß spricht. Zur Politik des Performativen. FaM: Suhrkamp.• Cherubim, D. (1991). Sprache und Aggression. Krieg im Alltag – Alltag und Krieg. Loccumer Protokolle, 58, 11-35.• Devkin, V. D. (1996). Der russische Tabuwortschatz. Leipzig: Langenscheidt Enzyklopädie.• Ehalt, Ch. (2015). Vorwort. In: Schmäh als ästhetische Strategie der Wiener Avantgarde, (S. 7-10). Suchy, I., Krejci, H. (Hg.).Weitra: Bibliothek der Provinz.• Ermen, I. (1996). Fluch – Abwehr – Beschimpfung. Pragmatik der formelhaften Aggression im Serbokroatischen. FaM u.a.: Peter Lang.• Faust, M. (1970). Metaphorische Schimpfwörter. Indogermanische Forschungen, 74, 57-47.• Fiehler, R. (1990). Kommunikation und Emotion. Berlin u.a.: Walter de Gruyter.• Freud, S. (1994). Der Humor. In: S. Freud Studienausgabe Bd. IV, (S. 275-282). A. Mitscherlich, J. Strachey, A. Richards (Hg.). FaM: Fischer.• Gauger, H-M. (2012). Das Feuchte und das Schmutzige. Kleine Linguistik der vulgären Sprache. München: Beck.• Graber, H. G. (1931). Zur Psychoanalyse des Fluchens. Psychoanalytische Bewegung, 3, 57-68.• Havryliv, O. (2009). Verbale Aggression. Formen und Funktionen am Beispiel des Wienerischen. FaM, Wien u.a.: Peter Lang.• Herrmann, S. K., Krämer, S., Kuch, H. (Hg.). (2007). Verletzende Worte. Die Grammatik sprachlicher Missachtung. Bielefeld: Transcript.• Hess-Lüttich, E.W.B. (2008). HimmelHerrgottSakrament! Gopfridstutz! und Sacklzement! Vom Fluchen und Schimpfen – Malediktologische Beobachtungen. Kodikas/Code. An International Journal of Semiotics, 31(3-4), 327-337.• Holzinger, H. (1984). Beschimpfungen im heutigen Französisch. Pragmatische, syntaktische und semantische Aspekte. Ph.D. Dissertation: Universität Salzburg.• Kiener, F. (1983). Das Wort als Waffe. Zur Psychologie der verbalen Aggression. Göttingen: Vandenhoek & Ruprecht.• Kotthoff, H., Jashari, S., Klingenberg, D. (2013). Komik (in) der Migrationsgesellschaft. Konstanz und München: UVK Verlagsgesellschaft.• Krämer, S. (Hg.) (2010). Gewalt in der Sprache. Rhetoriken verletzenden Sprechens. München: Wilhelm Fink.• Liebsch, B. (2007). Subtile Gewalt. Weilerswirt: Velbrück Wiss.• Lötscher, A. (1980). Lappi, Lööli, blööde Siech! Schimpfen und Fluchen im Schweizerdeutschen. Frauenfeld: Huber.• Mokienko, V., Walter, H. (1999). Lexikographische Probleme eines mehrsprachigen Schimpfwörterbuchs. Anzeiger für slawische Philologie, XXVI, 199-210.• Opelt, I. (1965). Die lateinischen Schimpfwörter und verwandte sprachliche Erscheinungen. Heidelberg: Winter.• Rehbock, H. (1987). Konfliktaustragung in Wort und Spiel. Analyse eines Streitgesprächs von Grundschulkindern. In: Konflikte in Gesprächen, (S. 176- 238). G. Schank, J. Schwitalla (Hg.). Tübingen: Gunter Narr.• Schumann, H. B. (1990). Sprecherabsicht: Beschimpfung. Zeitschrift für Phonetik, Sprachwissenschaft und Kommunikationsforschung, 43, 259-281.• Schwarz-Friesel, M. (2013). Sprache und Emotion. Tübingen und Basel: Francke.• Searle, J. R. (1971). Sprechakte. Ein sprachphilosophischer Essay. FaM.: Suhrkamp.• Sornig, K. (1975). Beschimpfungen. Grazer Linguistische Studien, 1, 150- 170.• Stavyc´ka, L. (2008). Ukraїns´ka mova bez tabu. Slovnyk necensurnoї leksyky ta її vidpovidnykiv [Ukrainian language without taboo. Dictionary of abusive vocabulary and its correspondence]. Kyiv: Klassyka.• Wierzbicka, A. (1973). Problems of expression: Their place in the semantic theory. In: Recherches sur les sestemes Signifiants. Symposium de Varsovie 1968, (S. 145-164). The Hague: Mouton.• Zhelvis, V.I. (1997). Pole brani: skvernosloviye kak socialnaya problema v yasykax i kulturax mira [Field of Battle: Foul Language as a Social Problem in the Languages and Cultures of the World]. Moscow: Ladomir.Джерела• Галкіна Є. У Кремлі не збираються доходити до Києва і Львова. Високий замок, 19. 02. – 25.02.15,6.• Ерофеев В. Русский апокалипсис. Retrieved from: Broyallib.ru/book/erofeev_viktor/ russkiy_apokalipsis html (12.02.2014).• Hessel, S. Empört euch! Retrieved from: http://jerome-segal.de/empoert_euch.pdf (27.02.2015).• Лагерлеф С. Чудесна мандрівка Нільса Гольгерсона з дикими гусьми / C. Лагерлеф. К: Веселка, 1991.• Лі Г. Вбити пересмішника / Г. Лі. К: Компанія Осма, 2015.• Майже половина українців вживає ненормативну лексику. Retrieved from http://life.pravda.com.ua/society/2013/09/25/139569/ (29.05.2013).• Путін хуйло. Retrieved from: https://uk.wikipedia.org/wiki/Путін_— _хуйло! (15.06.2016).Sources (translated and transliterated)• Galkina, J. U Kremli ne zbyrayutsia doхodyty do Kyiva i Lvova [The Kreml is not going to go to Kyiv or Lviv]. Vysokyj zamok, 19. 02. – 25.02.15,6.• Yerofeyev, V. Russkij apokalipsis [The Russian Apocalypse]. Retrieved from: Broyallib.ru/book/ erofeev_viktor/russkiy_apokalipsis html (12.02.2014).• Lagerlöf, S. (1991). Chudesna mandrivka Nilsa Holhersona z dykymy hus´my [The Wonderful Adventures of Nils]. Kyiv: Veselka.• Lee, H. (2015). Vbyty Peresmishnyka [To Kill a Mockingbird]. Kyiv: Kompania Osma.• Mayzhe polovyna ukraїnciv vzhyvaye nenormatyvnu leksyku [Almost half of Ukrainians use abusive vocabulary]. Retrieved from http://life.pravda.com.ua/society/2013/09/25/139569/ (29.05.2013).• Putin Xuylo [Putin is Asshole]. Retrieved from: https://uk.wikipedia.org/wiki/Путін_– _хуйло! (15.06.2016).